Rac1 promotes the survival of H9c2 cells during serum deficiency targeting JNK/c-JUN/Cyclin-D1 and AKT2/MCL1 pathways - Zhao, Jinlong (Int J Med Sci, 2018)
Rac1, known as a “molecular switch”, plays a crucial role in plenty of cellular processes. Rac1 aggravates the damage of myocardial cells in the process of myocardial ischemia-reperfusion during myocardial infarction through activating the NADPH oxidase and bringing about the reactive oxygen species(ROS) generation. Myocardial ischemia and hypoxia are the basic pathogenesis of myocardial infarction and the underlying mechanisms are intricate and varied. Moreover, the regulatory effect of Rac1 on myocardial cells in the condition of serum starvation and the potential mechanisms are still incompletely undefined. Therefore, heart-derived H9c2 cells cultured in 0% serum were used to mimic ischemic myocardial cells and to clarify the role of Rac1 in H9c2 cells and the underlying mechanisms during serum deficiency. After Rac1 was knocked down using specific siRNA, cell apoptosis was assessed by flow cytometry assay and cell proliferation was detected by CCK-8 assay and EdU assay. In addition, the expression and activation of protein in related signaling pathway were detected by Western blot and siRNAs was used to testify the signaling pathways. Our results indicated that Rac1 inhibited apoptosis, promoted proliferation and cell cycle progression of H9c2 cells during serum deficiency. We concluded that Rac1 inhibited apoptosis in an AKT2/MCL1 dependent way and promoted cell proliferation through JNK/c-JUN/Cyclin-D1.